Penerapan Metode Bernyanyi “Asyik” untuk Meningkatkan Motivasi Belajar pada Anak Usia Dini di Paud Al-Hikmah Desa Ciptamargi Kecamatan Cilebar Kabupaten Karawang - Iis Novianti; Sri Watini (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to increase children's learning motivation through the application of the "ASYIK" singing method. By applying the ASYIK play learning model with the ASYIK singing method hoped that it can increase children's motivation in following the learning process. The researcher took a Class Action Research with a sample that was consisting of 20 early childhood children in PAUD ALHIKMAH Ciptamargi Village, Cilebar District, Karawang Regency. This method consists of four stages; 1) the planning, 2). action, 3). Observation, and 4) reflection. Implementation in this activity is carried out in two cycles. The results of the study were shown by an increase in children's learning motivation from pre-cyclical which was only 35% or 7 out of 20 students who looked active and focused on following the learning process and the achievement of learning motivation was still in the category of very lacking, in the first cycle, 75% or 15 out of 20 students who looked so enthusiastic and excited about the achievement of learning motivation were still in the good category, and in cycle II it became 90% or 18 of the 20 learners who looked so enthusiastic and excited and the achievement of learning motivation became an excellent category.